2014
DOI: 10.3390/polym6041164
|View full text |Cite
|
Sign up to set email alerts
|

On the Interaction of Adherent Cells with Thermoresponsive Polymer Coatings

Abstract: Thermoresponsive polymer coatings allow the control of adhesion of cells on synthetic substrates. In particular, decreasing the temperature below the lower critical solution temperature (LCST) of the polymer triggers the non-invasive detachment of cells from their cultivation substrate. Widening the range of applications of these coatings in cellular biotechnology requires a better understanding of their interaction with cells. By monitoring the morphological changes of cells during their detachment at various… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 27 publications
0
14
0
1
Order By: Relevance
“…enzymes, chelators), magnetic or even stimuli‐responsive (e.g. thermo‐responsive, pH‐responsive, electro‐responsive, photo‐responsive).…”
Section: Introductionmentioning
confidence: 99%
“…enzymes, chelators), magnetic or even stimuli‐responsive (e.g. thermo‐responsive, pH‐responsive, electro‐responsive, photo‐responsive).…”
Section: Introductionmentioning
confidence: 99%
“…For PNIPAM it was shown that the extracellular matrix (ECM) was lifted off the surface by lowering the medium temperature, which rendered the surface protein repellent . By contrast, for brushes of poly‐2‐(2‐methoxyethoxy) ethyl methacrylate‐ co ‐oligo(ethylene glycol) methacrylate (poly(MEO 2 MA‐ co ‐OEGMA)) residual material was found on the surface after a temperature‐induced cell (sheet) release …”
Section: Introductionmentioning
confidence: 99%
“…[13,14] By contrast, for brushes of poly-2-(2-methoxyethoxy) ethyl methacrylate-co-oligo(ethylene glycol) methacrylate (poly (MEO 2 MA-co-OEGMA)) residual material was found on the surface after a temperature-induced cell (sheet) release. [15,16] The thermal trigger, which complements light, electric field, and pH changes as other known triggers of stimulus responsive polymers, is particularly interesting as a mild method in cell culture to control cell adhesion and detachment from biointerfaces. [17][18][19][20] The possibility to manipulate cells in culture without the use of enzymes is important for experiments in which downstream processes deal with surface proteins or cell-cell and cellmatrix connections.…”
Section: Introductionmentioning
confidence: 99%
“…Whereas the MA‐PEG‐LCNs were distributed all over the cells (Figure A, B), the TR‐LCNs showed selective localization surrounding and inside the cells. It has been reported before that thermoresponsive polymers are inclined to interact with the cell surface more selectively than others and is also found to mediate better cell internalizaton . Another possibility for this difference in distribution could be the bulkier MA‐PEG, which participates in extensive H‐bonding (due to the presence of hydroxyl moieties) in the cellular environment.…”
Section: Resultsmentioning
confidence: 93%